Eye therapy effects on visual stress based on electroencephalogram signals - Mat Safri, Norlaili (Penerbit UTM Press, 2015)
Eye therapy such as eye massages, has been designed to reduce eye problems and improve blood circulation of the eyes. When reading, the signs and symptoms of visual exhaustion are related to visual stress and people may make use of eye therapy to reduce this visual stress. It is well-known that a relaxed mind can be analysed via the study of an electroencephalogram signal. In this paper, we investigated the effect of eye therapy on visual stress by analysing brain signals (EEG) in frequency domain. Ten subjects participated. In the control task, subjects were asked to relax while EEG data were captured for two minutes. The next part was a visual test task, where the subjects were asked to search for a specific word in a text displayed on a computer screen while their EEG data were recorded. One visual test was performed without prior eye therapy, while the other three visual test tasks were performed following different eye therapy routines. The visual test task was completed fastest when subjects received eye drops and eye massages prior to the visual test. The difference between the visual test with and without prior eye therapy can be observed in the high-gamma frequency band, where with eye therapy, the high-gamma frequency band significantly increases in the frontal, temporal and occipital areas, and the word search performance was improved, with a shorter time needed to complete the task. In conclusion, the high-gamma frequency band may be an indicator to study visual stress, while specific eye-therapy routines may contribute to better eye and brain performance in word searching in a text displayed on a computer screen